(untitled) (Acta Entomologica Serbica, 2019)
Dengue (DEN) and yellow fever (YF) outbreaks have been previously reported in Nigeria. In order to avoid another epidemic, the identification of the vectors of these viruses at different locations is a necessity. Female adult mosquitoes caught in and around human dwellings in the Benue and Bayelsa States, Nigeria, using human-baiting and spray-sheet methods between January 2014 and December 2015, were examined for YF and DEN viruses usingreverse-transcription polymerase chain reaction (RT-PCR).In total 172,010 adult female mosquitoes were identified, put into 9,110 pools of mosquitoes and tested for YF and DEN viruses. The hourly biting activities, true infection rate (TIR) and the density of infected mosquitoes (DIM) were estimated for the species positive to YF and DEN viruses. Among twelve identified species – Aedes luteocephalus (Newstead, 1907), Ae. aegypti (Linnaeus, 1762), Ae. cumminsii Theobald, 1903, Ae. africanus (Theobald, 1901), Ae. albopictus (Skuse, 1894), Ae. vittatus (Bigot, 1861), Anopheles gambiae (Giles, 1902), A. nili Theobald, 1904, Mansonia africana (Theobald, 1901), M. uniformis (Theobald, 1901), Culex annulioris (Theobald,1901) and C. quinquefasciatus (Say,1823), three mosquito species, Ae. luteocephalus, Ae. aegypti and A. gambiae, were positive for YF in Oju and Ega, while DENV-3 was detected in samples of M. africana from Ikarama. The biting patterns of these positive mosquito species showed both day and night activities, except the population of A. gambiae from Ega, which typically demonstrated nocturnal activity extended until dawn/early morning hours. Ae. aegypti, A. gambiaeand Ae. luteocephalus could represent the primary vectors of YF in the Benue and Bayelsa States. The role of M. africana in transmitting DENV-3 also requires immediate investigation.